Campylobacteriosis in New Zealand: results of a case-control study. Issue 6 (December 1997) - Eberhart-Phillips, J; Walker, N; Garrett, N; Bell, D; Sinclair, D; Rainger, W; Bates, M
Abstract : STUDY OBJECTIVE: To identify and assess the contributions of major risk factors for campylobacteriosis in New Zealand. DESIGN: Case-control study. Home interviews were conducted over nine months using a standardised questionnaire to assess recent food consumption and other exposures. SETTING: Four centres in New Zealand with high notification rates of campylobacter infections–Auckland, Hamilton, Wellington, and Christchurch. PARTICIPANTS: Case patients were 621 people notified between 1 June 1994 and 28 February 1995 as having campylobacter infection. Control subjects were selected randomly from telephone directories, and were matched 1:1 with case patients in relation to sex, age group, and home telephone prefix. RESULTS: Risk of campylobacteriosis was strongly associated with recent consumption of raw or undercooked chicken (matched odds ratio 4.52, 95% confidence interval 2.88, 7.10). There was also an increased risk with chicken eaten in restaurants (matched odds ratio 3.85; 2.52, 5.88). Recent consumption of baked or roasted chicken seemed to be protective. Campylobacteriosis was also associated with recent overseas travel, rainwater as a source of water at home, consumption of raw dairy products, and contact with puppies and cattle, particularly calves. CONCLUSIONS: Improperly cooked chicken seems to be associated with a large proportion of campylobacteriosis in New Zealand. Thorough cooking of chicken in homes and restaurants could reduce considerably the incidence of this disease.